The analysis of permissible radial clearance in a piston-cylinder seal - A. G. Nikiforov; L. A. Muslova (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
In this research work, the influence of the radial clearance on the tightness coefficient of the working chamber with different cylinder diameters is considered. The main design scheme with the accepted assumptions is given. As a result of the study, recommendations are given for choosing the allowable radial clearance in the design and calculation of a reciprocating compressor.